2007
DOI: 10.1021/nl070693i
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nonequilibrium Phonon Populations in Single-Walled Carbon Nanotubes

Abstract: We studied spatially isolated single-walled carbon nanotubes (SWNTs) immobilized in a quasi-planar optical λ/2-microresonator using confocal microscopy and spectroscopy. The modified photonic mode density within the resonator is used to selectively enhance or inhibit different Raman transitions of SWNTs. Experimental spectra are presented that exhibit single Raman bands only. Calculations of the relative change in the Raman scattering cross sections underline the potential of our microresonator for the optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…8 Based on the simulations performed, the stress in the CNTs at various applied bias fields and varying diameters were estimated using Eq. (5). The results are shown in Figure 6.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…8 Based on the simulations performed, the stress in the CNTs at various applied bias fields and varying diameters were estimated using Eq. (5). The results are shown in Figure 6.…”
Section: Resultsmentioning
confidence: 94%
“…1 2 However, in a patterned array of CNT field emitters one observes fluctuation of collective field emission current, often with large spikes, and failure of CNTs. 3 4 Several studies have been reported, which shed light on various different possible mechanisms such as electrodynamic force activated failure in isolated CNT, 4 electron-phonon interaction effect causing degradation in emission current, 5 electrical breakdown 6 7 and thermal degradation of isolated CNTs. [8][9][10] Such degradation mechanisms have their origin in (i) the electro-mechanical force field leading to the deformation of CNTs and (ii) coupled electronphonon transport, thereby, producing temperature spikes under high electric field, and (iii) thermo-mechanically activated fracture of the tubular grapehene sheet.…”
Section: Introductionmentioning
confidence: 99%
“…In reciprocal space, the logarithmically diverging two-dimensional Van-Hove singularity at the hexagonal saddle (M) point [16] strongly enhances the generation and recombination of electron-hole pairs at the aS photon energy [10,17]. The SaS event is also expected to play a role in other low dimensional materials [18], where phase-space reduction becomes important.…”
mentioning
confidence: 99%
“…Cavity-controlled infrared emission originating from radiative electron-hole recombination in an individual SWCT is experimentally observed complementing studies of optically excited Raman scattering of cavity-confined SWCTs [6]. The resulting emission spectrum is narrowed by a factor of 7 with respect to the emission spectrum measured from the same SWCT in free (non-confined) space and is essentially determined by the quality (Q) factor of the photonic cavity.…”
Section: Introductionmentioning
confidence: 84%